SPECIFIC CHARACTERISTICS OF BACTRIA'S HELLENISM PERIOD - Bazarov Boris B. (Scholar Express Journal, 2023)
Bactria is an ancient center of civilization on the Great Silk Road was located and included the territories of presentday southern Tajikistan and Uzbekistan, and northern Afghanistan. Settlement and development of Hellenistic culture in ancient Bactria it belongs to III-II centuries B. C. During this period, the ancient culture that historically developed in the land of Bactria showed new features. This is especially expressed in architecture, ceramics and fine arts. Many conducted studies provide information on how the revival of urban planning and the emergence of new era cities, as well as the adoption of new styles in urban planning and architecture, took place today in the land of Ancient Bactria
Keywords: today; historically; Ancient; Bactria